Differential cardiovascular risk profiles by sex among adults with CKD: a NHANES-based analysis - Belikoff, Hannah T.; Walsan, Ramya; Hildreth, Cara M.; Phillips, Jacqueline K. (Frontiers in Cardiovascular Medicine, 2025)
IntroductionChronic kidney disease (CKD) and cardiovascular disease are closely interconnected, with cardiovascular disease the leading cause of death for those with CKD. This increased risk for those with CKD is partly attributed to shared risk factors between the conditions. These risk factors differ in presentation between females and males; however, further research is needed to better understand how sex influences cardiovascular risk factors among individuals with CKD.MethodsData from the National Health and Nutrition Examination Survey (NHANES) from 2007 to 2018 was utilised. CKD was classified as an albumin-to-creatinine ratio ≥30 mg/g or an estimated glomerular filtration rate (eGFR) <60 ml/min/1.73 m2. Participants were categorized into GFR categories based on their eGFR results for further analysis. Two-way ANOVAs compared means across groups, and a Tukey's post hoc test was performed to assess the statistical significance between group means. Multivariable logistic regression was used to determine the association between cardiovascular risk factors and sex among individuals with and without CKD.ResultsA total of 30,804 participants aged 20 years and older were included, in which 5,528 were classified as having CKD. Our analyses of participants by sex and GFR categories revealed that for both females and males, as renal function declined, systolic blood pressure increased while haemoglobin and haematocrit levels decreased. Multivariate logistic regression revealed that females with CKD demonstrated reduced odds for diabetes (OR: 0.53, CI: 0.42–0.66), hypertension (OR: 0.80, CI: 0.66–0.97), low haematocrit (OR: 0.47, CI: 0.40–0.56), and elevated triglycerides (OR: 0.75, CI: 0.63–0.88), yet exhibited increased odds of a high waist circumference (OR: 1.69, CI: 1.40–2.04) and low high-density lipoprotein cholesterol (HDL-C) (OR: 1.18, CI: 1.00–1.39), compared to males with CKD.ConclusionSex-based differences in cardiovascular risk factors among individuals with CKD reveal that females have lower odds of diabetes, hypertension, low haematocrit and elevated triglycerides, but higher odds of increased waist circumference and low HDL-C compared to males. These findings highlight the need to incorporate sex-specific perspectives into CKD research and management to improve personalized care.